International Human Rights Obligations within the States System: The Avoidance Account - Montero, Julio César (2017)
This essay proposes an original account of international obligations for human rights and their priority: the avoidance account. This view holds that the present states system is legitimate morally acceptable only if the international community undertakes all feasible measures to avert the risks its coercive enforcement creates for the enjoyment of human rights. Under present conditions this implies discharging four international human rights obligations which are constructed as duties of justice, rather than as humanitarian duties or duties of beneficence. After discussing two cosmopolitan arguments that support the tenet that the international order must maximize human rights satisfaction to the extent possible, the essay proceeds to develop the avoidance account, expound its main implications, and contrast it with alternatives in the literature to show its benefits.